GPS total electron content (TEC) and position range rate error using Malaysia data / Norsuzila Ya'acob, Azita Laily Yusof and Mohd Tarmizi Ali - Ya'acob, Norsuzila; Yusof, Azita Laily; Ali, Mohd Tarmizi (2012)
The integral of electron density along the path, known as Total Electron Content (TEC) is a major source of GPS positioning error, ever since the turn off of Selection Availability (SA) in year 2000. Ionization process is mainly caused by solar radiation. Therefore, the density of electrons is very much dependant on location and time of the day, as well as season and sunspot cycle. This paper studied the TEC value for Malaysia regions, based on location of the receivers (latitude, longitude, height) and time of the day. The 13 locations of GPS receiver stations across West Malaysia were chosen and their TEC values were compared. The determination of the TEC value in ionosphere is done using ‘leveling’ process. In the process, the error translated from code-delay to the carrier-phase is assessed to reduce carrier phase ambiguities from the data. The positioning error can be calculated as one unit of TEC introduces a range error of approximately 0.16 meters at the L1 1.6GHz frequency of GPS. For this project, the calculated TEC range errors were from -3.1 meters to 7.2 meters at different receiver locations. In addition, for the 24 hours observation, the range errors varied from 1.4 meters to 6.6 meters, with the peak value at 15 hour local time and minimum at 1 hour local time